2000
DOI: 10.1080/10473289.2000.10464148
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring and Analysis of Hourly Solar UV Radiation in the 290-380 nm Range in the Middle Region of Saudi Arabia

Abstract: The UV and global solar radiation on a horizontal surface at ground level in Riyadh City (latitude 24 degrees 34' N, longitude 46 degrees 43' E) have been measured and analyzed. Measurements of UV radiation (295-385 nm) were recorded every 10 min for five years (January 1983-December 1987). The maximum recorded hourly mean irradiance UV radiation was 28 W/m2 and occurred in July, while the minimum was 14 W/m2 in December. A steady monthly value of [formula: see text] was obtained and equaled 2.9%. A similar tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…S3, available at Annals of Occupational Hygiene online). Long-term monitoring and analysis of solar radiation trends in SA have indicated that the solar radiation intensity increases with sunrise, reaching its maximum at 12 p.m., then decreases as the elevation of the sun decreases (Al-Dhafiri et al , 2000). Higher RH in the morning than in the afternoon is a result of the lower air temperature during the morning, which in turn decreases the ability of the air to hold water compared to later in the day (Davis et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…S3, available at Annals of Occupational Hygiene online). Long-term monitoring and analysis of solar radiation trends in SA have indicated that the solar radiation intensity increases with sunrise, reaching its maximum at 12 p.m., then decreases as the elevation of the sun decreases (Al-Dhafiri et al , 2000). Higher RH in the morning than in the afternoon is a result of the lower air temperature during the morning, which in turn decreases the ability of the air to hold water compared to later in the day (Davis et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The UV solar radiation is stronger in regions closer to the equator. In Riyadh, Saudi Arabia (25°N latitude), the maximum UV solar radiation was found to be up to 28 mW cm À2 at noon (28). Sabburg et al found a whole-day average of about 1 mW cm À2 day À1 in Toowoomba, Australia (28°S latitude), but unfortunately did not indicate the maximum UV solar radiation (29).…”
Section: Resultsmentioning
confidence: 99%
“…The UV solar radiation is stronger in regions closer to the equator. In Riyadh, Saudi Arabia (25°N latitude), the maximum UV solar radiation was found to be up to 28 mW cm −2 at noon . Sabburg et al .…”
Section: Resultsmentioning
confidence: 99%